PENGARUH PRODUCT DIVERSITY TERHADAP LOYALITAS KONSUMEN SKINCARE ONLINE - Dela Afiyana; Aflit Nuryulia Praswati (POLITEKNIK LP3I JAKARTA, 2024)
The beauty community in Indonesia is trendy, they will share information or tips and tricks about beauty and self-care through social media. This research aims to measure the influence of perceived security, customer experience, and product diversity on consumer satisfaction and loyalty. The study was carried out by distributing questionnaires to the people of Surakarta City and Sociolla customers and obtained as many as 100 respondents, and then processed using partial least squares (PLS) testing so that the results found that there were significant changes in direct influence through perceived security, customer experience and product diversity on consumer satisfaction. The findings also reveal that customer experience and consumer satisfaction can have a direct influence on consumer loyalty. However, differences such as perceived security, customer experience, and product diversity do not influence consumer loyalty. Key words: Perceived Security, Customer Experience, Product Diversity, Customer Loyalty, Customer Satisfaction